2018
DOI: 10.1016/j.cocis.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic substrates for cell biology

Abstract: The interactions of adherent cells with their insoluble extracellular matrices are complex and challenging to study in the laboratory. Approaches from interface science have been important to preparing models of the biological matrix wherein discreet ligands are immobilized and interact with cellular receptors. A recent theme has been to develop dynamic substrates, where the activities of immobilized ligands can be modulated in real-time during cell culture. This short opinion reviews the strategies to manipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Stimuli-responsive surfaces are a class of surface that can undergo pronounced changes in properties and functions, e.g. wettability, roughness, biointeractions, in response to an external stimulus or a change in the surrounding environment. , Such surfaces have attracted much attention in the biomedicine and biotechnology communities and have led to the concept of stimuli-responsive biointerfaces. , On the one hand, they provide a means of mimicking the dynamic interfacial molecular interactions involved in biological processes and are thereby useful in fundamental biological research. , On the other hand, they serve as tools for the modulation of biointerfacial interactions such as protein adsorption and cell adhesion and have great potential for practical applications including bioseparations, diagnostics, and cell culture. , In previous work on the design of stimuli-responsive biointerfaces, two approaches have been adopted: (i) modification with stimuli-responsive polymers (e.g., thermoresponsive poly­( N -isopropylacrylamide) (PNIPAAm)) to endow surfaces with responsive properties, and (ii) introduction of chemical components (e.g., host–guest couples, dynamic covalent bonds, and metal coordination pairs) that participate in reversible chemical interactions to control the presentation of bioactive ligands. , …”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive surfaces are a class of surface that can undergo pronounced changes in properties and functions, e.g. wettability, roughness, biointeractions, in response to an external stimulus or a change in the surrounding environment. , Such surfaces have attracted much attention in the biomedicine and biotechnology communities and have led to the concept of stimuli-responsive biointerfaces. , On the one hand, they provide a means of mimicking the dynamic interfacial molecular interactions involved in biological processes and are thereby useful in fundamental biological research. , On the other hand, they serve as tools for the modulation of biointerfacial interactions such as protein adsorption and cell adhesion and have great potential for practical applications including bioseparations, diagnostics, and cell culture. , In previous work on the design of stimuli-responsive biointerfaces, two approaches have been adopted: (i) modification with stimuli-responsive polymers (e.g., thermoresponsive poly­( N -isopropylacrylamide) (PNIPAAm)) to endow surfaces with responsive properties, and (ii) introduction of chemical components (e.g., host–guest couples, dynamic covalent bonds, and metal coordination pairs) that participate in reversible chemical interactions to control the presentation of bioactive ligands. , …”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, thiol anchors are connected to the substrates that bind to gold surfaces. This principle was extensively demonstrated using hydroquinone electrogens by Mrksich and coworkers [ 78 , 79 ]. The authors observed that the rates of enzymatic hydrolysis of gold immobilized ester substrates can be measured in real time voltametrically with no adverse effect on the assay caused by immobilization.…”
Section: Classification Of Synthetic Enzyme Substratesmentioning
confidence: 99%
“…Changes in these interactions as a consequence of the ECM remodeling give rise to specific cell signaling and intracellular cascades, consequently triggering relevant cell behaviors like adhesion, migration, proliferation, differentiation, and apoptosis . To mimic the above dynamic interactions in artificial matrices, sophisticated synthetic biointerfaces, which are capable to reversible display bioactive ligands and dynamic modulating specific cell-biomaterial interactions, have attracted increasing attentions in both fundamental cell biology and tissue engineering. In addition, the controlled interactions of membrane receptors with ligands immobilized on a biomaterial are also relevant in molecular targeting and isolation methods in medical diagnostics and therapeutics. , …”
Section: Introductionmentioning
confidence: 99%